Bela Lugosi Meets a Brooklyn Gorilla - Enger, Charles Van.; Cahn, Philip; Duke, Maurice, 1910-1996; Beaudine, William, 1892-1970; Ryan, Tim, 1899-1956; Lugosi, Bela, 1882-1956; Mitchell, Duke; Petrillo, Sammy; Landers, Muriel, 1921-1977; Hazard, Dick; Van Enger, Charles J., 1890-1980.; Digiview Productions (Digiview Productions, 2004)
A mad scientist meets a team of Martin-and-Lewis imitators in a jungle and turns one of them into a gorilla.
Compatible with all DVD players.
Videodisc release of the 1952 motion picture.
Cinematography, Charles Van Enger ; film editing, Philip Cahn ; original music, Richard Hazard ; art direction, James W. Sullivan ; set decoration, Edward G. Boyle ; costume design, Wesley Jeffries, Esther Krebs ; executive producer, Jack Broder.
Bela Lugosi, Duke Mitchell, Sammy Petrillo, Muriel Landers.
DVD; stereo.; standard full frame.
113514
Keywords: Comedy films; Feature films; Mad scientist films